CREATIVE AND COLLECTIVE SOCIAL MARKETING ORIENTATIONS AS DRIVERS OF PHYSICAL ACTIVITY BEHAVIOR: MEDIATING ROLE OF SELF-EFFICACY - Kaswan; Umi Narimawati; Luki Adiati Pratomo (INJOSEDU: International Journal of Social and Education, 2026)
Physical inactivity remains a significant public health concern among government employees, who are often exposed to sedentary working conditions. This study aimed to examine the effects of Creative Social Marketing Orientation (Creative SMO), Collective Social Marketing Orientation (Collective SMO), and Self-Efficacy (SE) on Physical Activity Behavior (PAB) among government employees in West Java, Indonesia. A quantitative cross-sectional survey was conducted involving 276 employees from provincial, district, and city governments. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling (PLS-SEM). The results demonstrated that creative SMO had a positive and significant direct effect on PAB, while Collective SMO showed no significant direct effect. SE was found to be a significant predictor of PAB. In addition, SE significantly mediated the relationships between both Creative SMO and  PAB and Collective SMO and PAB. These findings highlight the critical role of SE as a psychological mechanism through which SMO influence PAB. Creative SMO can promote physical activity both directly and indirectly, whereas collective- SMO primarily operate through enhanced SE. The findings also provide practical implications for workplace health promotion programs that seek to foster active lifestyles through creative, participatory, and supportive organizational environments.